Digital Connectivity and Economic Development: The Role of Social Media in Selected ASEAN Economies - Saira Mahroof; Dr. Muhammad Shabbir; Muhammad Akmal (Social Science Review Archives, 2025)
The research study investigates the impact of social media on the economic development of the selected Asian countries for a time period of 2009-2022. The analysis is conducted on panel data based on a quantitative design in 21 countries by using the PCSE estimator and Two-Stage Least Squares (2SLS) design to minimize potential endogeneity. Furthermore, the Panel Quantile Regression (PQR) was employed in depicting heterogeneity in the levels of income. These results show that there is a positive correlation between social media penetration and economic performance that is statistically significant as social media penetration increases by 1 percentage point resulting into a respective increase in GDP per capita of 0.056%. This is particularly stronger in the more well-to-do economies, which is why there is a necessity to make more access to digital and boost technological possibilities. The results are significant in the point of the centrality of social media with reference to a sharing of knowledge, market growth, and innovation- areas, which directly affect economic growth in a region. Analytical policy implications are also there that the government of the Asian nations should intensify and expand the broadband infrastructure, enhance digital literacy, and offer plausible regulatory frameworks to allow the maximum advantage of the digital platform and diminish the bottlenecks like misinformation. The current study contributes to the existing literature by investigating the impact of social media on the growth of the economies at various levels. It offers new empirical evidence on the potential that digital interconnection can play in terms of maintaining and fair economic growth in regions that differ sharply with Western economies regarding digital potential and institutional capability.